2016
DOI: 10.1158/0008-5472.can-15-1737
|View full text |Cite
|
Sign up to set email alerts
|

A Breakthrough: Macrophage-Directed Cancer Immunotherapy

Abstract: Successful immunotherapy of cancer is becoming a reality aided by the realization that macrophages play an important role in the growth or regression of tumors. Specifically, M2/repair-type macrophages predominate in human cancers and produce growth-promoting molecules that actively stimulate tumor growth in much the same way they help wounds heal. However, modulating M2/repair-type macrophages to M1/kill-type can slow or stop cancer growth. The effects involve direct activity of M1 kill-type as well as the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
261
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(263 citation statements)
references
References 26 publications
1
261
0
1
Order By: Relevance
“…Several macrophage-targeting agents that inhibit macrophage recruitment into tumor tissues and/or inhibit macrophage differentiation into the M2 pro-tumor phenotype are currently being investigated. [32][33][34][35] We previously reported that onionin A suppresses tumor progression by inhibiting M2 polarization of macrophages, which correlated with both tumor proliferation and immunosuppression 36,37 (Fig. 6).…”
Section: Discussionmentioning
confidence: 75%
“…Several macrophage-targeting agents that inhibit macrophage recruitment into tumor tissues and/or inhibit macrophage differentiation into the M2 pro-tumor phenotype are currently being investigated. [32][33][34][35] We previously reported that onionin A suppresses tumor progression by inhibiting M2 polarization of macrophages, which correlated with both tumor proliferation and immunosuppression 36,37 (Fig. 6).…”
Section: Discussionmentioning
confidence: 75%
“…43 On the other hand, the efficacy and efficiency of T cell-based immunotherapy are mainly dependent on the tumor microenvironment, in which macrophages play crucial roles. 44 Given their central regulation of immunosuppression, cancer stem cell development, angiogenesis and drug resistance, different strategies to target macrophages have being developed, including (1) inhibition of macrophage recruitment by blocking CCL2 or CSF1/CSF1R signaling; (2) pharmacological depletion of macrophages through the administration of bisphosphonates or liposomal encapsulated clodronate; (3) reprogramming macrophages from M2 to M1 like phenotype by the intravesical instillation of Mycobacterium bovis (bacillus Calmette-Guerin), which stimulates the cytotoxic activity of macrophages to treat superficial bladder cancer. In addition, a broad variety of nanoparticle systems (NPs) has been developed with the aim of delivering drugs to solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor micro-environment contains cells that are helping the tumor to expand and to evade the immune system such as cancer-associated fibroblasts, MDSCs, M2 and Tregs [29]. The important role of macrophages in tumor progression and the possibilities to target these cells were reviewed previously [30,31]. Targeting these tumor-resident immune suppressive myeloid cells could be an option to improve immunotherapy [30][31][32].…”
Section: Treatment Of Advanced or End-stage Cancer May Fail Due To Immentioning
confidence: 99%
“…The important role of macrophages in tumor progression and the possibilities to target these cells were reviewed previously [30,31]. Targeting these tumor-resident immune suppressive myeloid cells could be an option to improve immunotherapy [30][31][32]. Hence, it is no surprise that specifically mono-immunotherapy -focused on reinforcing the tumor-specific T-cell response -as a last resort therapy is often not successful.…”
Section: Treatment Of Advanced or End-stage Cancer May Fail Due To Immentioning
confidence: 99%